2007
DOI: 10.1002/14651858.cd001434.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatments for fungal infections of the skin and nails of the foot.

Abstract: Topical treatments for fungal infections of the skin and nails of the foot..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 94 publications
2
87
0
9
Order By: Relevance
“…ciclopiroxolamine after 48 weeks. This might be due to a lack of compliance because of repetitive daily applications over months [9]. The number of treatment sessions might be the great advantage of the laser treatment; they are short, and the dermatologist can ensure the treatment is performed accurately.…”
Section: Discussionmentioning
confidence: 99%
“…ciclopiroxolamine after 48 weeks. This might be due to a lack of compliance because of repetitive daily applications over months [9]. The number of treatment sessions might be the great advantage of the laser treatment; they are short, and the dermatologist can ensure the treatment is performed accurately.…”
Section: Discussionmentioning
confidence: 99%
“…Mild to moderate tinea pedis usually responds to topical antifungal agents. A meta-analysis of 11 randomized trials concluded that treatment with topical allylamines (terbinafine, naftifine, butenafine) results in a slightly higher cure rate than topical imidazoles (ketoconazole, econazole, clotrimazole) [60]. Chronic, extensive, or refractory disease is treated with a topical agent plus oral terbinafine (250 mg daily for 2 weeks; 86 % mycologic cure), itraconazole (200 mg twice daily for 1 week; 67 % mycologic cure), or fluconazole (150 mg once weekly for 2-6 weeks; 77 % clinical cure) [61][62][63][64].…”
Section: Tinea Pedismentioning
confidence: 99%
“…Nail infections, however, require prolonged application (at least one year) and studies are scarce. [9] Resistance of the dermatophytes…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Kolbe electrolysis od dicarboxylic acids 149 and UA 1. 710 www.chemsuschem.org 9 Other applications UA was evaluated as a thermal storage material absorbed in wallboard. The purpose was to diminish heat fluctuations in buildings by modifying the wall material with 20-30 % organic material.…”
Section: Undecylenic Acid In Food Chemistrymentioning
confidence: 99%